PENGARUH STRES KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI (Studi pada Kantor Kecamatan Turi Kabupaten Lamongan) - Tri fita Khoirotun Muaffifah; Abdul Kodir Djaelani; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRAKThe aim of this research is to find out of the influence of stress work, work environment against the performance of employees in partial and simultaneous. This method of using the quantitative, the kind of this research was causal comperative research. A sample of this research is civil servants district Turi district Lamongan the numberet in 33 respondents. The data collection using the questionnaire. The analyst used in this study is linear regression analysis multiple with SPSS 16.0 for windows. 1. The results of research shows that : there are the influence of a significant positive and stress work employees. 2. There are the influence of positive and significant work environment against the performance of the servants. Keyword : performance employee, stress work, work environment.